The Application of Question-Answer Centered Theory in Chemistry Teaching - Wu, Zhifu (Technium BioChemMed, 2020)
The question-answer centered theory is another important discovery after the three major theories of modern education (student centered theory, subject centered theory and culture centered theory), and it is also the divergence of educational models between western countries and Eastern countries. Problem centered teaching is a theme of quality education in recent years. Its core ideas mainly include: starting from problems, carrying out innovative questions, cultivating problem awareness; taking problems as a link, running through all links of "preparation, speaking, practice, assistance and examination" in chemistry teaching; cultivating creative thinking and solving problems.